Malaria Control and Medical Services in Cilacap Under Dutch Colonial Rule In the Early 20th Century - Ilham Nur Utomo; Fauzan Syahru Ramadhan; Khairana Zata Nugroho; Desi Susanti (PURBAWIDYA, 2026)
This study examines health problems and healthcare services in Cilacap Regency in relation to malaria outbreaks during the Dutch colonial period in the early 20th century. Cilacap was known as the largest port in southern Java yet faced numerous complex health problems. This study employs the historical method, which is categorized into four stages: heuristics, source criticism, interpretation, and historiography. In analyzing the research problems, biopower theory is used, which positions the role of the Dutch colonial government in controlling biological aspects and public health. The findings of this study indicate that the health of Cilacap Regency’s population was under threat from diseases, particularly malaria. Inadequate environmental conditions were one of the main factors in the spread of malaria. Furthermore, efforts to eradicate malaria through healthcare services remained limited. The Dutch colonial government’s health interventions were solely aimed at serving their economic interests. This made Cilacap Regency one of the areas with the lowest quality of public health despite the implementation of the Dutch Ethical Policy and economic activities at Cilacap Port.